Microhabitat preferences of vulnerable plants in the Genus Saurauia (Actinidiaceae) on the slopes of Talaga Bodas, West Java, Indonesia - DIANA HERNAWATI; RITA FITRIANI; RINALDI RIZAL PUTRA; DIKI MUHAMAD CHAIDIR (Society for Indonesian Biodiversity, 2025)
Abstract. Hernawati D, Fitriani R, Putra RR, Chaidir DM. 2025. Microhabitat preferences of vulnerable plants in the Genus Saurauia (Actinidiaceae) on the slopes of Talaga Bodas, West Java, Indonesia. Biodiversitas 26: 1511-1518. Saurauia is a genus of ecologically significant plants, with several species classified as vulnerable due to habitat degradation and environmental changes. Despite their conservation importance, studies on their habitat preferences remain limited, particularly in montane ecosystems. This study aims to investigate microhabitat preferences of Saurauia species on the slopes of Talaga Bodas, West Java, Indonesia, an area renowned for its rich biodiversity shaped by complex topography and montane ecosystems. This study focuses on examining essential environmental factors such as elevation, light intensity, temperature, humidity, and soil pH affecting the distribution and habitat preferences of these at-risk plants. Field surveys recorded the occurrence of Saurauia species in various microhabitats, which was subsequently analyzed using Canonical Correspondence Analysis (CCA) to clarify the connection between environmental factors and species distribution. Three species were identified including S. microphylla and S. bracteosa, both endemic in Java, and S. cauliflora, widespread in Java and Bali, and the IUCN Red List classifies all three species as vulnerable. According to the survey, clear microhabitat preferences were reported, including S. cauliflora which flourishes at lower elevations where light intensity is high and temperatures are warmer, S. microphylla occupies higher elevations that are cooler and more humid, while S. bracteosa shows adaptability to moderate conditions. This study provides critical insights into habitat needs, informing conservation strategies that enhance habitat diversity, ecosystem stability, and mitigate environmental pressures. Safeguarding the unique microhabitats of Talaga Bodas is essential for ensuring the long-term survival of these vulnerable plant species.